Optimization Of Bench Blast Design With The Aid Of Computer (febe1846-7d11-4969-9dc5-f8d6a8a628b1) - Wei Wu (International Conference on Ground Control in Mining, 1992)
A new bench blast design method and its realization with the assistance of the computer is introduced. The basic design principle is to define a rhomb cell, called fully-fractured zone, through a series of full scale bench crater tests and apply this geometric pattern in multi-hole, multi-row blast design. To illustrate the design method, the optimization process and assessment of blast performance are presented in the context of a case study.